Ankyloblepharon filiforme adnatum in trisomy 18 Edwards syndrome. Issue 11 (November 1990) - Evans, D G; Evans, I D; Donnai, D; Lindenbaum, R H
Abstract : Three cases of ankyloblepharon filiforme adnatum (AFA) in infants with Edwards syndrome are described. The case for a fifth subgroup of AFA is reinforced.